2019
DOI: 10.3389/feduc.2019.00026
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of STEM Professional Development on Teachers' Knowledge, Self-Efficacy, and Practice

Abstract: Research frameworks outline key aspects of STEM (science, technology, engineering, mathematics) integration for teachers, but translating this research into productive changes in teachers' classroom practices remains a challenge, particularly in schools without an emphasis on STEM integration. In this article, we detail how a STEM education descriptive framework was used to design and enact a year-long professional development with eight middle and secondary teachers at non-STEM focused schools in Southeast US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 15 publications
5
46
0
1
Order By: Relevance
“…Engineering-focused Professional Development Numerous studies have reported on the positive influences of engineering PD on teachers' engineering teaching efficacy (Gardner et al, 2019;Utley et al, 2019), understanding of engineering design (Yoon et al, 2013), engineering content knowledge (Duncan et al, 2011;Macalalag et al, 2010;Zarske et al, 2004), and science content knowledge (Macalalag et al, 2010;Utley, Ivey, Hammack, & High, 2019;Zarske et al, 2004). These and other studies have led to the development of a few engineering-specific PD models that guided the design of the PD used in the current study.…”
Section: Methodological Concerns With Drawing-based Instrumentsmentioning
confidence: 99%
“…Engineering-focused Professional Development Numerous studies have reported on the positive influences of engineering PD on teachers' engineering teaching efficacy (Gardner et al, 2019;Utley et al, 2019), understanding of engineering design (Yoon et al, 2013), engineering content knowledge (Duncan et al, 2011;Macalalag et al, 2010;Zarske et al, 2004), and science content knowledge (Macalalag et al, 2010;Utley, Ivey, Hammack, & High, 2019;Zarske et al, 2004). These and other studies have led to the development of a few engineering-specific PD models that guided the design of the PD used in the current study.…”
Section: Methodological Concerns With Drawing-based Instrumentsmentioning
confidence: 99%
“…The results of studies conducted by Gardner et al (2019) and Lee and Lee (2019) indicate that instructional efficacy has a mediating effect on the relationship between the enhancement of instructional expertise and attitudes toward STEAM education. In particular, in school education, integration and linkages between subjects have become increasingly important, and in Korea, the revised curriculum for middle and high schools has been applied in 2020, and teachers must develop new capabilities to adapt to these changes.…”
Section: Technology Subjects and Steam Educationmentioning
confidence: 98%
“…Educational change receptivity directly and positively affects the improvement of instructional expertise (Cho, 2006;Meyer & Herscovitch, 2001), and efforts to improve instructional expertise have a positive effect on attitudes toward STEAM education (Morrison, 2006;Uslu & Bumen, 2012;van Aalderen-Smeets & Walma van der Molen, 2015). In addition, prior studies of the relationship between the improvement of instructional expertise and efficacy indicate that efforts to improve instructional expertise have a positive effect on efficacy (Gardner et al, 2019;Morrison, 2006;van Aalderen-Smeets & Walma van der Molen, 2015) and that instructional efficacy has a direct and static effect on attitudes toward STEAM education (Ashton, 1984;Bandura, 1997;Koballa & Crawley, 1985;Martin et al, 2001). Summarizing the above, it can be seen that school educational change receptivity has a mediating effect on the relationship between teachers' instructional resource collaboration and attitudes toward STEAM education, and school educational change receptivity and instructional expertise can be seen as having a double mediating effect.…”
Section: Technology Subjects and Steam Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a rich literature supporting the need for STEM PD in K-12 education as well as for researching PD approaches and their effectiveness in education settings. Numerous studies report that participating in engineering-focused PD can increase teachers' engineering content knowledge (Duncan et al, 2011;Macalalag et al, 2010), understanding of engineering design (Yoon et al, 2013), and teaching efficacy (Utley et al, 2019;Gardner et al, 2019). Goodnough et al (2014) employed action research to investigate PD aimed at enhancing STEM integration in elementary school settings.…”
Section: Professional Developmentmentioning
confidence: 99%